(untitled) (Medical Forum Monthly, 2021)
Objective: To know the frequency of HIV infection among tuberculous patients, presenting to tertiary care hospitals in Khyber Pakhtunkhwa. Study Design: Descriptive study Place and Duration of Study: This study was conducted at Departments of Medicine in two tertiary level hospitals (Lady Reading Hospital Peshawar and Madan Medical complex Mardan in Khyber Pakhtunkhwa (KPK) from 1st October 2020 to 31st March 2021. Materials and Methods: KPK is one of the four provinces of Pakistan situated on the northwest part of the country. KPK has an area of 101,741 Km2 and comprises of thirty five districts. The estimated population was 35.53 million in the year 2017. These two hospitals provide clinical care, diagnostic and treatment services to TB and HIV infected individuals. Patients are referred from primary care physicians, private practitioners and TB centers. Results: Study population comprised of 160 patients. Frequency of HIV was 8.1%. Most affected age group was 51 to 60 years. Of the 13 HIV – Positive cases in tuberculous patients, 10(76.9%) patients had pulmonary TB, whereas 03(23.0%) cases had extra pulmonary TB, including 02(66.6%) cases of tuberculouspleuritis and 01(33.3%) patient of TB lymphadenitis. Conclusion: All newly diagnosed tuberculous patients should be assessed and screened for HIV co-infection